(Gas Chromatographic Identification of Java Citronella Oils (Andropogon Nardus Java de Jong) Using Methylphenylsyilicon, OV-17, Liquid Phase) - Salya Sait (Balai Besar Industri Agro, 1986)
The application of mthylphenylsilicon (OV-17)liquid phase to the gas-liquid chromatographic analysis of Java Citronella Oils (Andropogon nardus Java de Jong) is investigated. The result of analysis are compared with those obtained using Carbowax 20M liquid phase.